EARLY DIAGNOSTIC BIOMARKERS IN ACUTE ISCHEMIC STROKE: CLINICAL SIGNIFICANCE AND FUTURE PERSPECTIVES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Acute ischemic stroke (AIS) is a leading cause of mortality and long-term disability worldwide. Rapid and accurate diagnosis is critical for effective treatment and improved patient outcomes. Neuroimaging remains the gold standard for diagnosis; however, it may be limited by availability, cost, and time constraints. Consequently, there is growing interest in identifying reliable early diagnostic biomarkers that can facilitate prompt diagnosis, guide therapeutic decisions, and predict prognosis. This article reviews current knowledge regarding early diagnostic biomarkers in acute ischemic stroke, including inflammatory markers, neuronal injury biomarkers, glial markers, endothelial dysfunction indicators, and microRNAs. The clinical significance, diagnostic accuracy, and future perspectives of these biomarkers are discussed, highlighting their potential role in precision medicine and stroke management.